A novel homozygous sequence variant in GLI1 underlies first case of autosomal recessive pre‐axial polydactyly. Issue 4 (8th January 2019) - Ullah, Asmat; Umair, Muhammad; Majeed, Ayesha I.; Abdullah,; Jan, Abid; Ahmad, Wasim
Abstract :